2016
DOI: 10.2147/ott.s105664
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib induces autophagic cell death and differentiation in acute myeloblastic leukemia

Abstract: Lapatinib is an oral-form dual tyrosine kinase inhibitor of epidermal growth factor receptor (EGFR or ErbB/Her) superfamily members with anticancer activity. In this study, we examined the effects and mechanism of action of lapatinib on several human leukemia cells lines, including acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and acute lymphoblastic leukemia (ALL) cells. We found that lapatinib inhibited the growth of human AML U937, HL-60, NB4, CML KU812, MEG-01, and ALL Jurkat T cells. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Previous studies have reported that lapatinib induces autophagic cell death in acute myeloblastic leukemia-derived cell lines ( 17 ); however, we did not detect any changes in the levels of autophagy markers ATG5, ATG7, and LC3II following lapatinib treatment. These contradictory results could be attributed to variations in the concentrations of lapatinib, differences in the time points used in the experiments, cell status, and variations in other experimental factors.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported that lapatinib induces autophagic cell death in acute myeloblastic leukemia-derived cell lines ( 17 ); however, we did not detect any changes in the levels of autophagy markers ATG5, ATG7, and LC3II following lapatinib treatment. These contradictory results could be attributed to variations in the concentrations of lapatinib, differences in the time points used in the experiments, cell status, and variations in other experimental factors.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, several studies have reported the use of lapatinib in the treatment of leukemia; for example, lapatinib induces apoptosis in cell lines derived from acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) ( 15 ), and it has been shown to regulate autophagy, apoptosis, and megakaryocytic differentiation in K562 cells ( 16 ). In addition, lapatinib promotes autophagic cell death and differentiation in AML ( 17 ). Importantly, lapatinib inhibits cell proliferation and promotes cell apoptosis in Philadelphia chromosome-positive acute lymphoblastic leukemia ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that ERBB2 inhibits autophagy via the formation of a complex with Beclin 1, which is a key regulator of autophagy 40 . In addition, lapatinib, a dual tyrosine kinase inhibitor of EGFR and ERBB2, induced autophagic cell death in breast cancer cells overexpressing ERBB2 40 , human hepatoma cells 41 , and acute myeloblastic leukemia 42 . In the present study, circ-GRB10 could regulate ERBB2 expression by sponging miR-328-5p.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that vacuoles in AML blasts may represent dysfunctionally enlarged autophagosomes or other cellular organelles. Indeed, Chen et al (2016) detected a similar blast vacuolization in vitro when treating AML U937 cell lines with lapatinib and demonstrated that these vacuoles appear with lapatinib-induced autophagic cell death [25]. Nevertheless, the blasts require a more detailed ultrastructural analysis and further studies are needed to confirm our findings in a larger cohort and to determine whether this morphological feature can be useful in clinical routine.…”
Section: Discussionmentioning
confidence: 52%